Regulation of transcription factors by the epigallocatechin-3-gallate in poultry reared under heat stress - Şahin, Kazım; Smith, M. O. (Taylor & Francis Ltd, 2016)
High ambient temperature is associated with decreasing growth rate, egg production, feed efficiency, nutrient utilisation, egg quality and is a major problem resulting in extensive economic losses in poultry. Poultry reared under heat stress may exhibit various metabolic disorders caused by a chronic state of oxidative stress and inflammation. Recently, nuclear factor-erythroid 2-related factor 2 (Nrf2) has emerged as an agent that plays a significant role in cellular protection against oxidative stress and inflammation. The nuclear factor kappa-B (NF-kappa B) signalling pathway has been associated with enhanced inflammatory response and its activation has been significantly correlated with heat stress. These transcription factors when activated can regulate antioxidant and anti-inflammatory cellular responses leading to the expression of detoxifying enzymes. Studies have shown that NF-kappa B and Nrf2 expression can be modulated by several factors, such as bioactive compounds. Green tea contains many polyphenolic antioxidants including the catechin, epigallocatechin-3-gallate (EGCG). As bioactive compounds, supplementing EGCG in poultry diets may improve antioxidant status in poultry. EGCG modulates signalling pathways including the NF-kappa B and Nrf2 that regulate antioxidant and anti-inflammatory responses. This review aims to discuss the evidence to justify a recommendation of EGCG in heat stressed poultry as a non-pharmacological option to activate the NF-kappa B and Nrf2 pathways.
Keywords: heat stress; EGCG; antioxidant; anti-inflammatory; poultry